Spacecraft attitude control: development and application of new algorithms - Abdelrahman, Mohammad; Hassan, Sayed (LAMBERT Academic Publishing, 2012)
The main goal of the research is to collect and develop new attitude algorithms that build up the different scenarios acted by a spacecraft starting from the orbit injection phase. It is found that the attitude scenarios can be classified mainly into two categories the first is the angular momentum management of a spacecraft and the second is the attitude maneuvers. The first category can be divided into two modes which are the detumbling mode and the momentum unloading mode. A new algorithm for estimating the angular rates has been developed. In the second category, the attitude maneuver, the research work is concluded by developing a new technique to solve the problem of the second category using neuro-fuzzy control.